Products and coke from the conversion of bio-oil acids, esters, aldehydes and ketones over equilibrium FCC catalysts - Bertero, Melisa Paola (2013)
Reactivity and product distributions in the conversion of five different compounds representing typical species in bio-oils were studied over an equilibrium FCC catalyst at 500 °C during 60 s in a fixed bed reactor. Acetic acid, methyl acetate, furfural, 3-methyl-2-pentanone and 2-hidroxy-3-methylcyclopentenone were dissolved at 5% wt. in water. Thermal conversions were performed under the same conditions with inert SiC in the bed. The test compounds converted very differently, deoxygenation being produced by decarboxylation and dehydration. Furfural and 3-methyl-2-pentanone gave the highest yields of hydrocarbons, with high selectivity to light olefins and, when liquid (case of ketones), to aromatics. Methyl acetate gave the highest yield of oxygenated compounds. Coke yields were important (maximum 12.8% wt., 2-hidroxy-3-methylcyclopentenone). Thermal conversions were similar to the catalytic ones with acetic acid and methyl acetate, and much lower for the other reactants. Compared catalytic experiments, the thermal yields of hydrocarbons were much higher with acetic acid, and the yields of oxygenated higher with methyl acetate ester. Much less hydrocarbons were produced thermally with the other reactants. This information may be useful for predicting contributions if these compounds are to be co-processed in existing FCC units or upgraded over acidic catalysts.